2020
DOI: 10.3390/ijms21072535
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Up-Regulation of SERCA2a Exacerbates RyR2-Dependent Ventricular and Atrial Arrhythmias

Abstract: Ryanodine receptor 2 (RyR2) and SERCA2a are two major players in myocyte calcium (Ca) cycling that are modulated physiologically, affected by disease and thus considered to be potential targets for cardiac disease therapy. However, how RyR2 and SERCA2a influence each others’ activities, as well as the primary and secondary consequences of their combined manipulations remain controversial. In this study, we examined the effect of acute upregulation of SERCA2a on arrhythmogenesis by conditionally overexpressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…High level of SR Ca 2+ leak triggered by increased RyR2, together with upregulated NCX, could contribute to the pathogenesis of AF ( 37 ). Acute upregulation of SERCA2a by doxycycline in the setting of hyperactive RyR2 exacerbates dysregulated myocyte Ca 2+ handling and arrhythmogenesis in both ventricular and atrial myocardium in rodent model ( 38 ). However, overexpression of SERCA2a could suppress ERP shortening and AF induced by rapid pacing atrium in rabbit model ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…High level of SR Ca 2+ leak triggered by increased RyR2, together with upregulated NCX, could contribute to the pathogenesis of AF ( 37 ). Acute upregulation of SERCA2a by doxycycline in the setting of hyperactive RyR2 exacerbates dysregulated myocyte Ca 2+ handling and arrhythmogenesis in both ventricular and atrial myocardium in rodent model ( 38 ). However, overexpression of SERCA2a could suppress ERP shortening and AF induced by rapid pacing atrium in rabbit model ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…While these results clearly demonstrate a detrimental effect, the severe cardiomyopathy phenotype due to chronic SERCA overexpression masks the effect of the genetic manipulation on arrhythmias. A follow-up study from the same group conditionally overexpressed SERCA2a in the same CASQ2 KO mice and found that both atrial and ventricular arrhythmias were exacerbated due to acute upregulation of SERCA activity [75]. In contrast, in another study employing a different CPVT model of RyR2 knock in mouse (R4496C +/− ), upregulation of SERCA activity by knocking out its inhibitor PLN suppressed arrhythmias in vivo.…”
Section: Cellular Arrhythmogenesis: Sr Ca Loadmentioning
confidence: 98%
“…In fact, the acceleration of Ca 2+ uptake has been shown to promote rather than prevent arrhythmias attributable to SR overload. 14 In this context, an additional aim of this work is to gain insight into this mechanistic aspect by comparing the effects promoted by istaroxime and ouabain in cardiomyocytes lacking phospholamban (phospholamban‐knockout myocytes).…”
mentioning
confidence: 99%